Mademoiselle Chanel - Gortner, C. W. (William Morrow, an imprint of HarperCollinsPublishers, 2015)
A creative reimagining of the life of iconic fashion designer Coco Chanel traces the development of her exceptional sewing skills in an orphanage, her transformation into a couturier and the private struggles behind her subsequent fame.